Synthesis of ethane from CO 2 by a methyl transferase–inspired molecular catalyst - Suman Patra; Souvik Dinda; Soumili Ghosh; Triparna Roy; Abhishek Dey (Proceedings of the National Academy of Sciences, 2025)
Molecular catalysts with a single metal center are reported to reduce CO 2 to a wide range of valuable single-carbon products like CO, HCOOH, CH 3 OH, etc. However, these catalysts cannot reduce CO 2 to two carbon products like ethane or ethylene and the ability to form C–C from CO 2 remains mostly limited to heterogeneous material-based catalysts. We report a set of simple iron porphyrins with pendant thiol group can catalyze the reduction of CO 2 to ethane (C 2 H 6 ) with H 2 O as the proton source with a Faradaic yield >40% the rest being CO. The mechanism involves a CO 2 -derived methyl group transfer to the pendant thiol akin to the proposal forwarded for methyl transferases and a follow-up C–C bond formation of the thioether thus formed and a Fe(II)–CH 3 species generated by the reduction of a second molecule of CO 2 . The availability of a “parking space” in the molecular framework for the first reduced C 1 product from CO 2 reduction allows C–C bond formation resulting in a unique case where a component of natural gas can be generated from direct electrochemical reduction of CO 2 .